Strategi Humas Kai Divre III Dalam Menghadapi Isu Negatif - Muhammad Iqbal Dhio Fahrihan; Fifi Hasmawati; Sumaina Duku (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This thesis is entitled "KAI DIVRE III Public Relations Strategy in Facing Negative Issues" The development of technology has progressed greatly. Technology has penetrated into various fields, ranging from information, communication to transportation, one of which is Indonesian Railways. Every company including PT KAI (Persero) is required to continuously prepare itself to anticipate and adapt to the changes that occur. in an agency or company Public Relations is certainly very necessary and is one of the very important parts. With the right interaction with the public, the company can produce good public perception with the reputation and image of a company being positive in the eyes of the public. Recently, an accident occurred at a railroad crossing in Muara Enim Regency, South Sumatra. The incident involved an Avanza-type car and a Babaranjang train. The news quickly spread in the community, so that the news will certainly cause unpleasant issues, and will certainly cause different perceptions in the eyes of the community. From some comments on the post, many people have different views and misinterpretations and the author feels, such as one example that the author found in the comments column of the video uploaded by TribunJatim Official on YouTube. The formulation of the problem in this study is how the KAI DIVRE III Public Relations strategy in dealing with negative issues that develop in society. This research uses a qualitative approach Qualitative methods are used to obtain in-depth data, data that contains meaning. The data collection technique is documentation in the form of news related to research and in-depth interviews. The theory used in this research is the 4 principle models of Public Relations Strategy put forward by (M. Cutlip & Allen H. Center) 1. Fact Finding (Fact Finding), 2. Planning (Planning), 3. Action & Communication (Action and Communication), 4. Evaluating (Evaluation). From the results of the research, KAI DIVRE III Public Relations in dealing with negative issues uses the 4 Cutlip & Center principle models and each model has its own strategy and in each strategy it is running well.